IMPLEMENTATION OF SWOT ANALYSIS IN BUSINESS STRATEGY DEVELOPMENT: CASE STUDY AT BANK SYARIAH INDONESIA KCP JAKARTA ARTERI PONDOK INDAH - Eddy Irsan Siregar (RADJA PUBLIKA, 2024)
The objectives in this study are: 1) To determine the implementation process of SWOT analysis can affect the development of business strategy of Bank Syariah Indonesia KCP Jakarta Arteri Pondok Indah. 2) To find out the obstacles and challenges faced by Bank Syariah Indonesia KCP Jakarta Arteri Pondok Indah in adopting and implementing the results of SWOT analysis in the development of its business strategy, as well as strategies to overcome these obstacles. This research is a field research with a qualitative approach. The research data was obtained by direct interview techniques with information sources, namely managers and staff of Bank Syariah Indonesia KCP Jakarta Arteri Pondok Indah. The analysis method used is the Descriptive analysis method. The results of this study show that: 1) The implementation of SWOT analysis is significant for the business strategy of BSI KCP Jakarta Arteri Pondok Indah. The analysis identifies strengths, weaknesses, opportunities, and threats, enabling the bank to expand its customer base and overcome obstacles, such as geographical limitations. SWOT helps formulate adaptive strategies for business growth and service to customers. 2) Although the SWOT analysis provides valuable insights, BSI KCP Jakarta Arteri Pondok Indah faces obstacles, such as reliance on upper-middle class customers that limits portfolio diversification. The solution, expanding the customer base and product diversification. Intense competition in the Islamic and conventional banking industry is also a challenge; solutions, strengthen brand image, and develop innovative products.